Designing neuronal networks with chemically modified substrates: an improved approach to conventional in vitro neural systems - Maria M. Pardo-Figuerez (2018)
Highly organised structures have been well-known to be part of the complex neuronal network presented in the nervous system, where thousands of neuronal connections are arranged to give rise to critical physiological functions. Conventional in vitro culture methods are useful to represent simplistic neuronal behaviour, however, the lack of such organisation results in random and uncontrolled neurite spreading, leading to a lack of cell directionality and in turn, resulting in inaccurate neuronal in vitro models. Neurons are highly specialised cells, known to be greatly dependent on interactions with their surroundings. Therefore, when surface material is modified, drastic changes in neuronal behaviour can be achieved. The use of chemically modified surfaces in vitro has opened new avenues in cell culture, where the chaotic environment found in conventional culture methods can be controlled by the combination of surface modification methods with surface engineering techniques. Polymer brushes and self-assembled monolayers (SAMs) display a wide range of advantages as a surface modification tool for cell culture applications, since their properties can be finely tuned to promote or inhibit cellular adhesion, differentiation and proliferation. Therefore, when precisely combined with patterning techniques, a control over neuronal behaviour can be achieved. Neuronal patterning presents a system with instructive cues that can be used to study neuron-neuron communication by directing single neurites in specific locations to initiate synapses. Furthermore, although this area has not been much explored, the use of these patterned brushes could also be used in co-culture systems as a platform to closely monitor cell heterotypical communication. This research demonstrates the behaviour of SH-SY5Y neurons on a variety of SAMs and polymer brushes, both in isolation and combination to promote cellular spatial control. APTES and BIBB coatings promoted the highest cell viability, proliferation, metabolic activity and neuronal maturation, whilst low cell adhesion was seen on PKSPMA and PMETAC surfaces. Thereafter, PKSPMA brushes were used as a potential cell repulsive coating and its combination with micro- patterning techniques (photolithography and soft lithography) resulted in a system with instructive cues for neuronal guidance, where neuronal directionality was obtained. In the final chapter of this thesis, a chimeric co-culture system was developed where the patterned SH-SY5Y cells were co-cultured with C2C12 myoblasts in an attempt to obtain an organised neuronal-muscle co-culture system. Whilst preliminary observations showed first stages of a patterned neuronal-muscle co-culture, future work is necessary to refine and improve the patterned co-culture process.